2011
DOI: 10.1186/1751-0147-53-30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaplasma phagocytophilum infection and effect on lamb growth

Abstract: BackgroundA major challenge in sheep farming during the grazing season along the coast of south-western Norway is tick-borne fever (TBF) caused by the bacteria Anaplasma phagocytophilum that is transmitted by the tick Ixodes ricinus.MethodsA study was carried out in 2007 and 2008 to examine the prevalence of A. phagocytophilum infection and effect on weaning weight in lambs. The study included 1208 lambs from farms in Sunndal Ram Circle in Møre and Romsdal County in Mid-Norway, where ticks are frequently obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…We observed that lambs that developed clinical signs of TBF had a slightly lower weight gain at later time points (Week 6 and 15) compared to clinically healthy lambs. In accordance with our results, weight reduction as a consequence of an A. phagocytophilum infection has been indicated in several studies (Stuen et al, 1992, Stuen et al, 2002Grøva et al, 2011). Hence, sheep farmers may experience both indirect loss (i.e.…”
Section: Tbf and Body Weightsupporting
confidence: 92%
“…We observed that lambs that developed clinical signs of TBF had a slightly lower weight gain at later time points (Week 6 and 15) compared to clinically healthy lambs. In accordance with our results, weight reduction as a consequence of an A. phagocytophilum infection has been indicated in several studies (Stuen et al, 1992, Stuen et al, 2002Grøva et al, 2011). Hence, sheep farmers may experience both indirect loss (i.e.…”
Section: Tbf and Body Weightsupporting
confidence: 92%
“…In contrast, earlier studies indicate a weight reduction of 1.4-3.8 kg in the autumn between seropositive and seronegative lambs [26,27]. An earlier report also indicates that spring treatment of ewes and lambs with cypermectin pour-on produced 6% more lambs at weaning and the treated lambs were 1.5 kg heavier than untreated lambs [28].…”
Section: Discussionmentioning
confidence: 92%
“…Abortion in ewes and reduced fertility in rams have also been reported. In addition, reduced weight gain in A. phagocytophilum infected bullocks and lambs have been observed (Taylor and Kenny, 1980; Stuen et al, 1992; Grøva et al, 2011). …”
Section: Clinical Characteristicsmentioning
confidence: 99%